PENGARUH PARTISIPASI ANGGARAN, EVALUASI ANGGARAN, DAN KESULITAN PENCAPAIAN TUJUAN ANGGARAN TERHADAP KINERJA APARAT PEMERINTAH DAERAH (STUDI EMPIRIS PADA SKPD WALIKOTA JAKARTA BARAT) - Swarmilah Hariani; Veny Veny (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2018)
This study aims to examine the Influence of Budget Participation, Budget Evaluation, and Difficulty of Achieving Budget Objectives on Local Government Apparatus Performance. The object of this research is the employees who have a role in the process of making and budgeting at 15 OPD (Organization of Regional Devices) located in West Jakarta Administration City. This study was conducted on 64 respondents using primary data through questionnaires distributed directly to the respondents. The method of analysis used in this study is multiple linear regression analysis. The results of this study indicate that the variables of budget participation and the difficulty of achieving the budget objectives have no effect on the performance of local government apparatus, while the Budget Evaluation has an effect on the performance of local government apparatus.